2008 3rd International Symposium on Communications, Control and Signal Processing 2008
DOI: 10.1109/isccsp.2008.4537388
|View full text |Cite
|
Sign up to set email alerts
|

Man-In-The-Middle attacks on bluetooth: a comparative analysis, a novel attack, and countermeasures

Abstract: We provide a comparative analysis of the existing MITM (Man-In-The-Middle) attacks on Bluetooth. In addition, we propose a novel Bluetooth MITM attack against Bluetoothenabled printers that support SSP (Secure Simple Pairing). Our attack is based on the fact that the security of the protocol is likely to be limited by the capabilities of the least powerful or the least secure device type. Moreover, we propose improvements to the existing Bluetooth SSP in order to make it more secure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…SSP uses four association models: OOB, Numeric Comparison, Passkey Entry, and Just Works (see Chap. However, it has been shown that MITM attacks against Bluetooth 2.1+EDR/3.0+HS/4.0 devices are possible by forcing the victim devices to use the Just Works association model [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (see Chap. The choice of association model depends on the device's IO capabilities (see Table 2.1 in Chap.…”
Section: Weaknesses In Association Models Of Sspmentioning
confidence: 99%
See 4 more Smart Citations
“…SSP uses four association models: OOB, Numeric Comparison, Passkey Entry, and Just Works (see Chap. However, it has been shown that MITM attacks against Bluetooth 2.1+EDR/3.0+HS/4.0 devices are possible by forcing the victim devices to use the Just Works association model [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (see Chap. The choice of association model depends on the device's IO capabilities (see Table 2.1 in Chap.…”
Section: Weaknesses In Association Models Of Sspmentioning
confidence: 99%
“…The attacking device is set to require authentication and encryption for each connection with the printer (see rows [14][15]. After the successful authentication with the printer (see rows [19][20][21][22][23][24][25], the attacking device abuses it by printing funny pictures, dozens of pages of random text, and various hoax documents (see rows [26][27][28]. After the successful authentication with the printer (see rows [19][20][21][22][23][24][25], the attacking device abuses it by printing funny pictures, dozens of pages of random text, and various hoax documents (see rows [26][27][28].…”
Section: Multithreatsmentioning
confidence: 99%
See 3 more Smart Citations